The birth of a Catholic Inuit community. The transition to Christianity in Pelly Bay, Nunavut, 1935-1950 - Remie, Cornelius; Oosten, Jarich (Études/Inuit/Studies, 2002)
AbstractThe transition to Catholicism in Pelly Bay is usually described as a successful conquest of a pagan terra nullius, a process in which Inuit played only a passive role. In fact, there was already a nucleus of Catholics in Pelly Bay when the first missionary arrived. Inuit invited him to come and stay with them. This article describes the early years of the transition to Catholicism, as well as some religious, political and economic factors that played a part in this process. Missionary sources reveal that Inuit were by no means passive consumers, but active participants with their own interests and agendas. The missionaries appear to have been more concerned with the containment of the westward expansion of Anglicanism than the survival of paganism. Although the missionaries assumed leadership roles in many fields, they were often not aware of the extent to which Inuit continued traditional practices outside the scope of the missionaries. Moreover, many traditional practices were integrated into Christianity. Within the context of the Catholic Church, Inuit developed their own form of religiosity responding to their existential and cultural needs.